Study guides

☆☆

Q: What is 6x plus 1?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

6x - 9 + 2x + 1 = 8x -8

6x(1+4)

3x + 6x +1 = 10 9x = 10 - 1 9x = 9 x = 1

(6x + 1)(x + 13)

It is an expression that can be simplified to: 6x+1

Related questions

(6x + 1)(x + 1)

x= -1 y=-1

6x + 6v + 1 =6 (x + v) + 1

6x - 9 + 2x + 1 = 8x -8

2x + 9 = 6x + 1 9 - 1 = 6x - 2x 8 = 4x x = 2

Simple,its just like this: 6x+1+7-3 =6x+8-3 =6x+5

6x(1+4)

6x + 3 = 3(2x + 1)

-1 + 4x + 6x - 20 =10x - 19

-5x+1 = 6x -5x-6x = -1 -11x = -1 x = 1/11

3x + 6x +1 = 10 9x = 10 - 1 9x = 9 x = 1

(6x + 1)(x + 2)

People also asked